Public acceptance of default nudges to promote healthy and sustainable food choices - Dominic Lemken; Simone Wahnschafft; Carolin Eggers (Georg-August University of Göttingen, RTG 2654 Sustainable Food Systems, 2023)
Default nudges are an increasingly prominent tool for promoting healthy and sustainable food choices; however, questions of acceptance remain. While default nudges are more acceptable to the public than traditionally paternalistic tools that aim to restrict choice, they are also the least acceptable amongst nudging strategies. Little research has investigated the aspects of default nudge design that can be leveraged to better uphold freedom of choice, increase public acceptance, and therefore heighten legitimacy of default nudges. Consequently, this study examines public acceptance of five food choice default nudges with demonstrated precedent of effectiveness, as drawn from research studies and/or real-world policies, along with a design variation of each anticipated to increase acceptance. Three drivers of acceptance - perceived intrusiveness, perceived effectiveness, and own behavior - are examined.
Keywords: I12; I18; 330; default nudge; healthy and sustainable food choices; public acceptance; perceived intrusiveness; transparency